Pathways Linking Nicotinamide Adenine Dinucleotide Phosphate Production to Endoplasmic Reticulum Protein Oxidation and Stress - Gansemer, Erica R.; Rutkowski, D. Thomas (Frontiers in Molecular Biosciences, 2022)
The endoplasmic reticulum (ER) lumen is highly oxidizing compared to other subcellular compartments, and maintaining the appropriate levels of oxidizing and reducing equivalents is essential to ER function. Both protein oxidation itself and other essential ER processes, such as the degradation of misfolded proteins and the sequestration of cellular calcium, are tuned to the ER redox state. Simultaneously, nutrients are oxidized in the cytosol and mitochondria to power ATP generation, reductive biosynthesis, and defense against reactive oxygen species. These parallel needs for protein oxidation in the ER and nutrient oxidation in the cytosol and mitochondria raise the possibility that the two processes compete for electron acceptors, even though they occur in separate cellular compartments. A key molecule central to both processes is NADPH, which is produced by reduction of NADP+ during nutrient catabolism and which in turn drives the reduction of components such as glutathione and thioredoxin that influence the redox potential in the ER lumen. For this reason, NADPH might serve as a mediator linking metabolic activity to ER homeostasis and stress, and represent a novel form of mitochondria-to-ER communication. In this review, we discuss oxidative protein folding in the ER, NADPH generation by the major pathways that mediate it, and ER-localized systems that can link the two processes to connect ER function to metabolic activity.